High Performance MnO2 Nanoflower Electrode and the Relationship Between Solvated ion Size and Specific Capacitance in Highly Conductive Electrolytes - Izan Izwan, Misnon; Radhiyah, Abd Aziz; Nurul Khairiyyah, Mohd Zain; Vidhyadharan , Baiju; Syam, G. Krishnan; Rajan, Jose (Elsevier, 2014)
Flower shaped birnessite type manganese oxide (δ-MnO2) nanostructures are synthesized using a simple hydrothermal process with an aim to fabricate high performance supercapacitors for energy storage electrode. The studies reveal that layered δ-MnO2 had a basal plane spacing of ∼0.73 nm and are composed of thin nanosheets of thickness ∼23 nm. A detailed investigation is undertaken to draw a relationship between the solvated ion size of alkaline electrolytes (LiOH, NaOH and KOH) and pore size in the electrode material favoring high specific capacitance and faster electrode kinetics. The present work not only develops a high performance supercapacitive material but also identifies that by suitably tuning the sizes of solvated ion and the pores, supercapacitive behavior of a single material system can be tailored.